2015
DOI: 10.1007/s10552-015-0706-1
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric factors, adult weight gain, and mammographic features

Abstract: Adiposity seems positively associated with both dense and non-dense areas following adjustment for each other. Our findings suggest a higher breast dense area among women who gained weight and that a minimum of breast fat may be needed to promote the proliferation of this fibroglandular tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 43 publications
4
20
0
1
Order By: Relevance
“…The associations evaluated with these approaches could be compared with analyses carried out on area measurements partly adjusted for nondense area or for adiposity. This hypothesis is also reported in a recent analysis that we carried out among 1435 premenopausal and postmenopausal White women recruited at screening mammography ( Soguel and Diorio, 2016 ). We computed correlations between BMI, WC, WHR, and absolute dense area and found a negative correlation after adjustment for potential confounders, but not for variables reflecting adiposity ( r =−0.21; −0.23; and −0.19, respectively, P <0.0001).…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations
“…The associations evaluated with these approaches could be compared with analyses carried out on area measurements partly adjusted for nondense area or for adiposity. This hypothesis is also reported in a recent analysis that we carried out among 1435 premenopausal and postmenopausal White women recruited at screening mammography ( Soguel and Diorio, 2016 ). We computed correlations between BMI, WC, WHR, and absolute dense area and found a negative correlation after adjustment for potential confounders, but not for variables reflecting adiposity ( r =−0.21; −0.23; and −0.19, respectively, P <0.0001).…”
Section: Introductionsupporting
confidence: 81%
“…In contrast to the inconsistent results for the association between absolute nondense area and breast cancer risk, cross-sectional analyses on the association between absolute nondense area, or volume, and adiposity have shown a constant positive association for BMI ( Boyd et al , 1998 ; Maskarinec et al , 2001 ; Heng et al , 2004 ; Haars et al , 2005 ; Boyd et al , 2006 ; Guthrie et al , 2007 ; Irwin et al , 2007 ; Stone et al , 2009 ; Sung et al , 2010 ; Harris et al , 2011 ; Tseng and Byrne, 2011 ; Woolcott et al , 2011 ; Eng et al , 2014 ; Nayeem et al , 2014 ; Schetter et al , 2014 ; Soguel and Diorio, 2016 ), with correlation coefficients ranging from 0.41 to 0.77, percentage ( Boyd et al , 1998 ; Sung et al , 2010 ; Woolcott et al , 2011 ) or total ( Nayeem et al , 2014 ) body fat, and WC or WHR ( Sung et al , 2010 ; Tseng and Byrne, 2011 ; Woolcott et al , 2011 ; Nayeem et al , 2014 ; Soguel and Diorio, 2016 ). These results are not surprising because when adiposity is high, it can be expected that breast fat is also found in high amounts.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…A study of childhood weight/BMI identified an inverse association between mammographic density measures and BMI measured at ages 7–15 years with the strongest in late adolescence (20). Similarly, Soguel et al (27) found a negative correlation between BMI at 18 years of age and mammographic density, with correlations of −0.18 and −0.09 for PD and DA, respectively.…”
Section: Discussionmentioning
confidence: 73%